2016
DOI: 10.3109/24701394.2016.1143469
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis evidence of maternal lineages in Chinese Tibetan sheep using mtDNA D-loop panel

Abstract: The Tibetan sheep is an indigenous breed living in the entire Tibetan Plateau, and its origin and phylogenic relationships are still uncertain and controversial. In this study, we analyzed partial mtDNA D-loop sequences of 156 Chinese Tibetan sheep individuals from 12 distributed geographic ecotype populations. Phylogenetic analysis indicated that three maternal lineages (haplogroups A, B and C) were found in this breed and that Ovis vignei and Ovis ammon have possibly contributed to the original Tibetan sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Meadows et al [15], on the other hand, were the first to identify a fifth lineage (E) in the Tuj and Ivesi sheep breeds in a sample population consisting of Israeli Ivesi sheep and the Karakaş, Norduz, Morkaraman, Tuj, Çine Çaparı, Sakız, Karya, and Karayaka sheep breeds. In the Şavak breed that we investigated in this study, the D and E haplogroups were not found, but the A, B, and C haplogroups were identified, which are consistent with other similar studies [3,13,15,30,31]. The nucleotide diversity values identified in the Şavak Akkaraman breed were similar to those found by Pedrosa et al [13], but were lower than the 3 different domestic Chinese sheep breeds [32] and 13 domestic sheep breeds [3].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Meadows et al [15], on the other hand, were the first to identify a fifth lineage (E) in the Tuj and Ivesi sheep breeds in a sample population consisting of Israeli Ivesi sheep and the Karakaş, Norduz, Morkaraman, Tuj, Çine Çaparı, Sakız, Karya, and Karayaka sheep breeds. In the Şavak breed that we investigated in this study, the D and E haplogroups were not found, but the A, B, and C haplogroups were identified, which are consistent with other similar studies [3,13,15,30,31]. The nucleotide diversity values identified in the Şavak Akkaraman breed were similar to those found by Pedrosa et al [13], but were lower than the 3 different domestic Chinese sheep breeds [32] and 13 domestic sheep breeds [3].…”
Section: Discussionsupporting
confidence: 91%
“…The nucleotide diversity values identified in the Şavak Akkaraman breed were similar to those found by Pedrosa et al [13], but were lower than the 3 different domestic Chinese sheep breeds [32] and 13 domestic sheep breeds [3]. While the haplotype diversity found in the Şavak Akkaraman sheep is similar to that found by Zhao et al [32] in 3 different domestic Chinese sheep breeds, by Demirci et al [3] in 13 domestic Turkish sheep breeds, by Liu et al [33] and Guangxin et al [31] in Tibetan sheep, by Kuseniuk and Slota, [34] in Poland sheep, by Alonso et al [35] in Mexican Creole sheep, and by Nigussie et al [36] in Ethiopia sheep, the study that Chen et al [37] conducted in domestic Chinese sheep is lower than the Şavak Akkaraman breed. In other words, the haplotype diversity in the Şavak Akkaraman breed is higher.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Generally, indigenous domestic animals in Tibet are thought to have been introduced with the migration of Tibetan ancestors from northern China approximately 7,000 years ago [ 2 , 3 ]. Research based on mitochondrial DNA (mtDNA) revealed that Tibetan mastiff [ 4 ], Tibetan sheep [ 5 ] and Tibetan chicken [ 6 ] were derived from outside of Tibet, and Tibetan yak [ 7 ] and Tibetan pig [ 8 ] were appear to have a local origin. However, we currently have no direct genetic evidence regarding whether Tibetan horses originated in the region or were descended from exotic breeds.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial DNA sequence analysis led to the identification of five maternal haplotypes (A-E) that are currently recognised in various sheep populations around the world (Meadows et al, 2011). Tibetan sheep are believed to have descended from a combination of Ovis vignei, Ovis ammon (both of unknown haplotype) and animals of haplotypes A, B, and C (Guangxin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%